Clinical correlates and prognostic impact of binge-eating symptoms in major depressive disorder. (12th July 2022) - Olgiati, Paolo; Fanelli, Giuseppe; Atti, Anna Rita; De Ronchi, Diana; Serretti, Alessandro
Abstract : Binge-eating (BE) symptoms are relatively common in major depressive disorder (MDD), but their prognostic role is not fully understood. This study compared two groups of patients with MDD experiencing or not BE symptoms to ascertain differences in terms of clinical manifestations, presence of bipolar features, and antidepressant treatment outcomes. The study involved 482 outpatients collected within the Combining Medications to Enhance Depression Outcomes (CO-MED) trial, who were assessed with scales for depressive and hypomanic symptomatology, suicidality, comorbid mental disorders, and childhood traumas. BE symptoms were reported in 95 patients (20%). Patients with MDD experiencing BE symptoms were characterized by higher scores of negative self-outlook ( P = 0.0018), negative outlook of future ( P = 0.0014), irritability ( P = 0.0043), comorbid anxiety disorders (generalized anxiety disorder: P = 0.0006; panic disorder: P < 0.0001; social phobia: P < 0.0001), obsessive-compulsive disorder ( P = 0.0053), hypomanic symptoms (increased talkativeness: P = 0.0029; reduced need for sleep: P = 0.0171), and suicidality (suicidal propensity: P = 0.0013; suicidal risk: P = 0.0148; lifetime suicidal behavior: P = 0.0052). BE symptoms (OR = 2.02; 95% CI = 1.06–3.84) and depression severity (OR = 1.04; 95% CI = 1.00–1.08) were independently associated with lifetime attempted suicide. The presence of BE symptoms might indicate higher severity of depressive disorder. Suicidal risk is a major issue in these patients, whereas the association between BE and bipolar features needs further research.